Emerging and Re-Emerging Infections: A Challenge to Human Progress and Survival - Banneheke, H. (Sri Lanka Medical Association, 2015)
Introduction: The world is the home for a variety of micro-organisms and multiple hosts. Many interactions are taking place among them resulting in both favourable and unfavourable outcomes. Generally those adverse outcomes are caused by pathogenic micro-organisms. There are more than 1400 recognized pathogens in the world with over 12% of them being novel pathogens. With the increase of these novel pathogens or known pathogens, health professional and authorities identified the need for particular attention and intervention. Thus the term 'emerging and reemerging diseases' was introduced to highlight and warn the world about the impending threat from epidemics caused by these new pathogens. World Health Organization (WHO) has defined an emerging disease as "one that has appeared in a population for the first time, or that may have existed previously but is rapidly increasing in incidence or geographic range". For example Middle East Respiratory Syndrome Corona virus (MERS-CoV) which is sweeping the Arabic peninsula currently is a new pathogen. During the last decade, human plague has re-emerged (India - 1994/2002, Indonesia - 1997, Algeria - 2003), after a silent period of about 30-50 years.